Cost Effectiveness General Anesthesia Combined with Scalp Block Compared to General Anesthesia in Patients Undergoing Removal Tumor Craniotomyin Dr. Sardjito Hospital - Sudadi; Wicaksono, Galih Sahid; Uyun, Yusmein (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Background. Providers of anesthesia services have many opportunities to reduce these costs, of course with the aim of maintaining balance between profit, security and costs. Craniotomy surgery removal of the scalp block tumor is an alternative option that can be combined with general anesthesia. The scalp block itself can blunt stress response in craniotomy and can maintain unwanted hemodynamic instability. Purpose. Find out the cost effectiveness of the scalp block in craniotomy patients removing tumors at Dr. SARDJITO Hospital. Method. Method. Twenty patients ranging in age from 18 - 65 years with intracranial tumors who underwent tumor binding craniotomy at RSUP Dr. SARDJITO is grouped into two treatment groups with general anesthesia and general anesthesia with a combination of scalp blocks, both techniques are calculated using drugs and consumables during the operation. Results. Total cost on the general anesthesia combined scalp block was Rp. 1,347,276 lower Rp. 377,833 compared to general anesthesia Rp. 1,725,109 with a significant difference (p = 0.005). Similarly, the hourly cost of the group in the combined general anesthesia scalp block was Rp. 286,351 Rp. 97,107 lower than general anesthesia Rp. 383,457 with a significant difference (p = 0.038). Conclusion. Combination of general anesthesia and scalp block using 0.5% levobupivacaine more cost effective than general anesthesia and scalp block with placebo in supratentorial tumor patients undergoing tumor removal craniotomy.